Qualitative analysis of perceptions and experiences of emergency department staff in relation to implementation and outcomes of the Four‐Hour Rule/National Emergency Access Target in Australia. (4th September 2018) - Nahidi, Shizar; Forero, Roberto; McCarthy, Sally; Man, Nicola; Gibson, Nick; Mohsin, Mohammed; Mountain, David; Fatovich, Daniel; Fitzgerald, Gerard; Toloo, Ghasem (Sam); ,
Abstract: Objective: The implementation of the time target policy (Four‐Hour Rule/National Emergency Access Target [4HR/NEAT]) constituted a major change for ED, and potentially on quality of care. The present study aimed to understand perceptions and experiences of ED staff during 4HR/NEAT implementation. Methods: A semi‐structured interview was used to explore views and perceptions of 119 ED staff from 16 EDs in New South Wales, Australian Capital Territory, Queensland and Western Australia. The interviews covered aspects such as perceived changes in quality of clinical care, whether the capacity to deliver education was diminished or enhanced and whether the policy affected access to care. Interviews were transcribed, imported to NVivo 11 and analysed using content and thematic analysis. Results: Three themes were identified: quality and safety of care; access block and overcrowding; and medical education and training. Participants described both positive and negative aspects of the policy. Although some reported negative impacts on care quality and access block, more cited overall improvements in these areas. The majority perceived that medical education and training was negatively affected, mainly because of restricted training opportunities and reduced time for procedural skills. Conclusions: ED staff perceived important effects on quality and safety of care; access block and overcrowding; and medical education and training. In relation to an optimised ED role, quality of care and access block were overall felt to be improved, while education and training deteriorated. Our study increases understanding of the complexity of policy implementation processes and its impact on staff. Staff perceptions are a valuable measure of system performance and should be incorporated into system change evaluations.